DEVELOPING DIVISITE (DISCOVERY LISTENING WEBSITE) TO FACILITATE STUDENTS’ LEARNING IN LISTENING SUBJECT - Muhammad Fajar Hidayat; Dwi Putri Hartiningsari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This research aimed to develop DIVISITE (Discovery Listening Website) and facilitate students’ learning of the listening subject. The design of this research was educational R&D. The subjects of this study were the second-semester English Department students of STKIP PGRI Trenggalek for the academic year 2020/2021. The research procedure included needs analysis, studying education theories, developing the educational product, validating the product to experts, and field-testing. By using the website and combining it with the three stages in the Discovery Listening technique, it increased students' learning motivation and comprehension toward listening material. It was seen from the results of pre-motivation which obtained a score of 1051 (almost disagree). This implied that respondents rarely planned listening learning activities. Then, the results of the post-motivation questionnaire obtained a score of 1810 (almost agree). Thus, there was an increase related to students' learning motivation in listening by using the Discovery Listening Website. In conclusion, this research successfully developed DIVISITE (Discovery Listening Website) and facilitated students’ learning in listening. Furthermore, this research was able to achieve the research objectives, namely DIVISITE (Discovery Listening Website), to facilitate students learning in the listening subject.